THE EFFECT OF WORK STRESS ON STAFF PRODUCTIVITY DURING THE PANDEMIC PERIOD IN PT TELKOM AKSES NORTH JAKARTA - Allyfia Dhaneswari Prastowo; Anita Silvianita (JEMMA (Journal of Economic, Management and Accounting), 2021)
2020 was the year of the outbreak of the Covid-19 virus, which made things worse. The impact of the Covid-19 pandemic was also felt by employees of PT Telkom Akses North Jakarta which caused work stress which resulted in lowering the level of employee work productivity. This study aims to determine how much influence work stress has on employee work productivity. This research uses quantitative methods with the analysis technique used is simple linear regression. The population used is all employees of PT Telkom Akses and the sampling method is the probability sampling technique with the number of respondents is 68 respondents. Data collection techniques in this study are primary data using questionnaires and secondary data using literature study. The results of research conducted by researchers indicate that Work stress is in the good category, the Work Productivity variable is in the quite good category. From this research, it shows that there is a significant effect of Work stress on Work Productivity during the pandemic period at PT Telkom Akses. This shows that the higher the level of work stress, the lower the level of work productivity of PT Telkom Akses employees during the pandemic period.